(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
A numerical analysis of the influence of the geometry of a motor centrifugal pump on the formation of a cavitation cavity in the interblade space of its impeller is presented. A design has been developed for the impeller of a motor centrifugal pump with characteristics similar to this type of device. A geometric model has been constructed that has compact dimensions, has a correct pressure distribution in the section of the impeller, and is not subject to cavitation at a given operating mode. It is shown that with a relative increase in the outer radius of the impeller or a decrease in its width within 12–50% in comparison with a model close to that required for stable operation, cavitation occurs at the leading edge of the blade with subsequent growth throughout the entire volume of the flow part of the pump. A pump of this kind can be used as a hydrodynamic machine for the intensification of many chemical engineering processes due to the cavitation effect already at the stage of pumping liquid.